A high-barrier polypropylene sheet resistant to folding white and a preparation method thereof
Patent Information
- Application Number
- CN202611302383.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
然而,铝塑膜存在以下技术缺陷:1.成本高昂:铝塑膜制造工艺复杂,尤其是内层CPP(流延聚丙烯)专用料长期依赖进口,成本居高不下
[0022] 1. This invention successfully solves the problems of high cost, poor stamping formability, and difficult recycling of aluminum-plastic film. This invention not only possesses excellent barrier properties, effectively preventing moisture and oxygen intrusion and ensuring battery safety, but also exhibits good mechanical strength, meeting the stringent requirements of energy storage batteries for packaging materials. Furthermore, this invention exhibits no whitening during cold stamping, significantly improving the packaging appearance quality and meeting the aesthetic demands of high-end energy storage products.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials technology, and in particular to a fold-resistant, high-barrier polypropylene sheet and its preparation method. Background Technology
[0002] As the core component of electrochemical energy storage systems, energy storage batteries (such as lithium-ion batteries and sodium-ion batteries) have extremely stringent requirements for the performance of their packaging materials. These materials not only need excellent barrier properties to prevent the intrusion of moisture and oxygen, but also require good mechanical strength, resistance to electrolyte corrosion, and heat-sealing properties.
[0003] Currently, the mainstream packaging material for pouch batteries is aluminum-plastic composite film (referred to as aluminum-plastic film). Its typical structure includes a nylon outer layer (as a protective layer), an aluminum foil barrier layer (as a moisture / oxygen barrier layer), and a polypropylene (PP) heat-sealed inner layer. Due to its excellent mechanical properties and packaging reliability, aluminum-plastic film has become the mainstream packaging choice for pouch batteries. However, aluminum-plastic film has the following technical drawbacks: 1. High cost: The manufacturing process of aluminum-plastic film is complex, especially the inner layer CPP (cast polypropylene) material, which has long relied on imports, resulting in high costs. 2. Poor stamping formability: The aluminum foil layer is prone to pinholes and cracks during deep stamping, limiting its adaptability for packaging large-size or irregularly shaped batteries. 3. Difficult recycling: The composite structure of aluminum foil and plastic film is difficult to separate, making recycling after disposal difficult and costly.
[0004] To address the aforementioned shortcomings of aluminum-plastic films, the industry has proposed a technical approach of replacing them with multilayer co-extruded polypropylene films. For example, one patent discloses a polypropylene resin composition for battery packaging materials, but this composition primarily focuses on heat-sealing and electrolyte resistance, without fully considering the appearance issues during cold stamping. Another patent discloses a fold-resistant whitening polypropylene material, but it is mainly used in non-battery packaging fields such as home appliances and bags, and its barrier properties are insufficient to meet the long-term storage requirements of energy storage batteries. A key challenge commonly encountered in the cold stamping process of polypropylene sheets is "stress whitening" (also known as stress whitening or fold whitening). When PP sheets are bent, stretched, or stamped at room temperature, microcracks and silver streaks form inside the material, causing changes in the refractive index of light, resulting in localized whitening at the formed areas. While stress whitening does not affect the material's mechanical properties, it severely impacts the appearance quality of battery packaging, making it unacceptable in some energy storage products with strict appearance requirements (such as consumer electronics and high-end residential energy storage). Therefore, developing a PP packaging material that combines high barrier properties with cold stamping and non-whitening characteristics is an important direction for replacing existing aluminum-plastic films and achieving lightweight, low-cost, and green battery packaging.
[0005] Based on the above, this invention proposes a fold-resistant, high-barrier polypropylene sheet and its preparation method, which can effectively solve the above problems. Summary of the Invention
[0006] The purpose of this invention is to provide a fold-resistant, high-barrier polypropylene sheet and its preparation method.
[0007] To achieve the above objectives, the present invention provides a fold-resistant, high-barrier polypropylene sheet, wherein the fold-resistant, high-barrier polypropylene sheet is composed of the following raw materials in parts by weight: 65-85 parts of polypropylene matrix resin, 20-30 parts of ethylene-vinyl alcohol copolymer, 0.5-1.5 parts of silane coupling agent, 5-8 parts of toughening agent, 0.3-0.6 parts of lubricant, 0.2-0.6 parts of antioxidant, and 3-5 parts of compatibilizer.
[0008] Preferably, the polypropylene matrix resin is a composition of block copolymer polypropylene and homopolymer polypropylene in a weight ratio of 7:3.
[0009] Preferably, the toughening agent is at least one or a combination of two or more of ethylene octene elastomer (POE), ethylene propylene diene monomer (EPDM), hydrogenated styrene-butadiene block copolymer (SEBS), olefin block copolymer (OBC), and their grafts.
[0010] In one embodiment, the toughening agent is maleic acid-grafted ethylene octene elastomer (POE-g-MAH).
[0011] Preferably, the lubricant is one or a combination of two or more of calcium stearate, zinc stearate, polyethylene wax, and ethylene bis-stearamide.
[0012] In one embodiment, the lubricant is composed of zinc stearate and ethylene bis-stearamide in a weight ratio of 1:2.
[0013] Preferably, the antioxidant is a combination of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1.
[0014] Preferably, the compatibilizer is maleic anhydride-grafted polypropylene (PP-g-MAH).
[0015] Preferably, the silane coupling agent is a chlorinated silane coupling agent, which includes one of 3-chloropropylmethyldiethoxysilane, 3-chloropropylmethyldimethoxysilane, chloromethyltrimethylsilane, chloromethyldimethylchlorosilane, 3-chloropropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.
[0016] In one embodiment, the chlorine-containing silane coupling agent is 3-chloropropylmethyldimethoxysilane.
[0017] This invention application also provides a method for preparing a fold-resistant, high-barrier polypropylene sheet, the preparation method comprising the following steps:
[0018] (1) Place the EVOH granules in an 80℃ forced-air drying oven and dry at a constant temperature for 4-6 hours. Dissolve the silane coupling agent in an ethanol aqueous solution with a volume concentration of 70-75% to make the concentration of silane coupling agent in the mixture 8-9wt%. Put the dried EVOH into a high-speed mixer, then add the silane coupling agent ethanol solution and stir at high speed for 10-15 minutes. Then add the polypropylene matrix resin, lubricant, toughening agent, compatibilizer and antioxidant in sequence and dry mix in the high-speed mixer for 3-5 minutes.
[0019] (2) A co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 is used. The temperature range is set in 7 sections: Zone 1 185~195℃, Zone 2 200~210℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 215~225℃, Zone 6 210~220℃, and the die head 200~210℃. After the extruded molten strip is cooled and shaped in a 25~35℃ warm water bath, it is fed into a pelletizer to be cut into uniform granules of 3×3mm. The granules are then placed in an 80℃ drying oven for 2 hours to remove residual moisture on the surface and obtain blended granules.
[0020] (3) The blended granules are fed into a single screw sheet extruder. The barrel temperature is controlled at 190~225℃ and the die lip temperature is set at 210~220℃. After extrusion from the die lip, the material is directly fed into a three-roll calender. The three roll temperatures are set at 50℃, 45℃ and 40℃ respectively. After the shaped sheet is fully cooled by the cooling roller and trimmed, it is wound up to the set length to obtain a fold-resistant, high-barrier polypropylene sheet with a thickness of 0.2~2mm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. This invention successfully solves the problems of high cost, poor stamping formability, and difficult recycling of aluminum-plastic film. This invention not only possesses excellent barrier properties, effectively preventing moisture and oxygen intrusion and ensuring battery safety, but also exhibits good mechanical strength, meeting the stringent requirements of energy storage batteries for packaging materials. Furthermore, this invention exhibits no whitening during cold stamping, significantly improving the packaging appearance quality and meeting the aesthetic demands of high-end energy storage products.
[0023] 2. The materials used in this invention are less expensive, and due to its superior molding performance, it reduces the scrap rate during production, improves production efficiency, and further reduces manufacturing costs. Simultaneously, the recyclability of this invention solves the problems of high difficulty and cost in recycling aluminum-plastic film, aligning with the trends of green manufacturing and sustainable development.
[0024] 3. The widespread application of this invention will drive technological advancements and industrial upgrading in energy storage battery packaging materials, providing strong support for the widespread application of electrochemical energy storage systems. Particularly in consumer electronics and high-end energy storage, the application of this invention will enhance product competitiveness and meet market demand for high-quality, high-performance energy storage products.
[0025] 4. The raw materials for this invention are abundant and reasonably priced in China, which means that there are no high cost restrictions on its large-scale production; at the same time, the preparation method is simple and the overall production cost is not high, which is conducive to large-scale industrial production. Detailed Implementation
[0026] Example 1
[0027] (1) Place the EVOH granules in an 80℃ forced-air drying oven and dry at a constant temperature for 4 hours. Dissolve the silane coupling agent in an ethanol aqueous solution with a volume concentration of 70% to make the concentration of silane coupling agent in the mixture 9wt%. Put the dried EVOH into a high-speed mixer, then add the silane coupling agent ethanol solution and stir at high speed for 10 minutes. Then add the polypropylene matrix resin, lubricant, toughening agent, compatibilizer and antioxidant in sequence and dry mix in the high-speed mixer for 3 minutes.
[0028] (2) A co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 is used. The temperature range is set in 7 sections: Zone 1 185~195℃, Zone 2 200~210℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 215~225℃, Zone 6 210~220℃, and the die head 200~210℃. After the extruded molten strip is cooled and shaped in a 25~35℃ warm water bath, it is fed into a pelletizer to be cut into uniform granules of 3×3mm. The granules are then placed in an 80℃ drying oven for 2 hours to remove residual moisture on the surface and obtain blended granules.
[0029] (3) The blended granules are fed into a single screw sheet extruder. The barrel temperature is controlled at 190~225℃ and the die lip temperature is set at 210~220℃. After extrusion from the die lip, the material is directly fed into a three-roll calender. The three roll temperatures are set at 50℃, 45℃ and 40℃ respectively. After the shaped sheet is fully cooled by the cooling roller and trimmed, it is wound up to the set length to obtain a fold-resistant, high-barrier polypropylene sheet with a thickness of 0.2~2mm.
[0030] Example 2
[0031] (1) Place the EVOH granules in an 80℃ forced-air drying oven and dry at a constant temperature for 6 hours. Dissolve the silane coupling agent in an ethanol aqueous solution with a volume concentration of 75% to make the concentration of silane coupling agent in the mixture 8wt%. Put the dried EVOH into a high-speed mixer, then add the silane coupling agent ethanol solution and stir at high speed for 15 minutes. Then add the polypropylene matrix resin, lubricant, toughening agent, compatibilizer and antioxidant in sequence and dry mix in the high-speed mixer for 5 minutes.
[0032] (2) A co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 is used. The temperature range is set in 7 sections: Zone 1 185~195℃, Zone 2 200~210℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 215~225℃, Zone 6 210~220℃, and the die head 200~210℃. After the extruded molten strip is cooled and shaped in a 25~35℃ warm water bath, it is fed into a pelletizer to be cut into uniform granules of 3×3mm. The granules are then placed in an 80℃ drying oven for 2 hours to remove residual moisture on the surface and obtain blended granules.
[0033] (3) The blended granules are fed into a single screw sheet extruder. The barrel temperature is controlled at 190~225℃ and the die lip temperature is set at 210~220℃. After extrusion from the die lip, the material is directly fed into a three-roll calender. The three roll temperatures are set at 50℃, 45℃ and 40℃ respectively. After the shaped sheet is fully cooled by the cooling roller and trimmed, it is wound up to the set length to obtain a fold-resistant, high-barrier polypropylene sheet with a thickness of 0.2~2mm.
[0034] Example 3
[0035] (1) Place the EVOH granules in an 80℃ forced-air drying oven and dry at a constant temperature for 6 hours. Dissolve the silane coupling agent in an ethanol aqueous solution with a volume concentration of 75% to make the concentration of silane coupling agent in the mixture 9wt%. Put the dried EVOH into a high-speed mixer, then add the silane coupling agent ethanol solution and stir at high speed for 15min. Then add the polypropylene matrix resin, lubricant, toughening agent, compatibilizer and antioxidant in sequence and dry mix in the high-speed mixer for 5min.
[0036] (2) A co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 is used. The temperature range is set in 7 sections: Zone 1 185~195℃, Zone 2 200~210℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 215~225℃, Zone 6 210~220℃, and the die head 200~210℃. After the extruded molten strip is cooled and shaped in a 25~35℃ warm water bath, it is fed into a pelletizer to be cut into uniform granules of 3×3mm. The granules are then placed in an 80℃ drying oven for 2 hours to remove residual moisture on the surface and obtain blended granules.
[0037] (3) The blended granules are fed into a single screw sheet extruder. The barrel temperature is controlled at 190~225℃ and the die lip temperature is set at 210~220℃. After extrusion from the die lip, the material is directly fed into a three-roll calender. The three roll temperatures are set at 50℃, 45℃ and 40℃ respectively. After the shaped sheet is fully cooled by the cooling roller and trimmed, it is wound up to the set length to obtain a fold-resistant, high-barrier polypropylene sheet with a thickness of 0.2~2mm.
[0038] Comparative Example 1
[0039] Weigh the specific raw materials according to Table 1. The difference from Example 3 is that the silane coupling agent is the fluorinated silane coupling agent 3,3,3-trifluoropropylmethyldimethoxysilane.
[0040] Comparative Example 2
[0041] Weigh the specific raw materials according to Table 1. The difference from Example 3 is that the silane coupling agent is silane coupling agent KH550.
[0042] Comparative Example 3
[0043] Weigh the specific raw materials according to Table 1. The difference from Example 3 is that the silane coupling agent is silane coupling agent KH560.
[0044] Comparative Example 4
[0045] Weigh the specific raw materials according to Table 1. The difference from Example 3 is that the silane coupling agent is silane coupling agent KH570.
[0046] Table 1
[0047]
[0048] Performance testing
[0049] All were prepared into sheets with a thickness of 0.4 mm for performance testing.
[0050] Tensile strength and elongation at break were determined according to the method in GB / T 1040.3-2006.
[0051] The flexural modulus was determined in accordance with GB / T 9341-2008.
[0052] The notched impact strength of the cantilever beam was determined in accordance with GB / T 1843-2008.
[0053] Oxygen permeability and water vapor permeability were determined in accordance with GB / T 1038-2022 and GB / T 1037-2021, respectively.
[0054] The 90° bend whitening test is performed by bending the object 90° at room temperature and observing the result.
[0055] The specific measurement results are shown in Tables 2 and 3.
[0056] Table 2
[0057]
[0058] Table 3
[0059]
[0060] As shown in Table 3, the oxygen permeability of Example 3 is lower than that of the other comparative examples, indicating that the material has extremely low permeability to oxygen and water vapor, effectively blocking the penetration of gases and moisture. This is attributed to the addition of ethylene-vinyl alcohol copolymer in the formulation, which has excellent gas barrier properties and can significantly improve the material's ability to block oxygen and water vapor. In the examples, under different formulation ratios, both oxygen and water vapor permeability remained at low levels, indicating that the material's barrier performance is stable and unaffected by minor adjustments to the formulation, providing reliable gas and moisture barrier protection for practical applications.
[0061] In Table 3, the 90° bending whitening test of Examples 1 to 3 showed "no whitening", indicating that the material is not prone to whitening when subjected to bending and has good stress whitening resistance. Compared with the "slight whitening" in some comparative examples, the stress whitening resistance of the examples is more outstanding and can better meet the application scenarios with high requirements for material appearance and performance stability.
[0062] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.
Claims
1. A fold-resistant, high-barrier polypropylene sheet, characterized in that, The fold-resistant, high-barrier polypropylene sheet is composed of the following raw materials in parts by weight: The composition includes 65-85 parts of polypropylene matrix resin, 20-30 parts of ethylene-vinyl alcohol copolymer, 0.5-1.5 parts of silane coupling agent, 5-8 parts of toughening agent, 0.3-0.6 parts of lubricant, 0.2-0.6 parts of antioxidant, and 3-5 parts of compatibilizer.
2. The fold-resistant, high-barrier polypropylene sheet according to claim 1, characterized in that, The polypropylene matrix resin is a combination of block copolymer polypropylene and homopolymer polypropylene.
3. The fold-resistant, high-barrier polypropylene sheet according to claim 2, characterized in that, The polypropylene matrix resin is a composition of block copolymer polypropylene and homopolymer polypropylene in a weight ratio of 7:
3.
4. The fold-resistant, high-barrier polypropylene sheet according to claim 1, characterized in that, The toughening agent is at least one or a combination of two or more of ethylene octene elastomer (POE), ethylene propylene diene monomer (EPDM), hydrogenated styrene-butadiene block copolymer (SEBS), olefin block copolymer (OBC), and their grafts.
5. The fold-resistant, high-barrier polypropylene sheet according to claim 1, characterized in that, The lubricant is one or a combination of two or more of calcium stearate, zinc stearate, polyethylene wax, and ethylene bis-stearamide.
6. The fold-resistant, high-barrier polypropylene sheet according to claim 5, characterized in that, The lubricant is composed of zinc stearate and ethylene bis-stearamide in a weight ratio of 1:
2.
7. The fold-resistant, high-barrier polypropylene sheet according to claim 1, characterized in that, The antioxidant is a combination of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:
1.
8. The fold-resistant, high-barrier polypropylene sheet according to claim 1, characterized in that, The silane coupling agent is a chlorinated silane coupling agent, which includes one of 3-chloropropylmethyldiethoxysilane, 3-chloropropylmethyldimethoxysilane, chloromethyltrimethylsilane, chloromethyldimethylchlorosilane, 3-chloropropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.
9. The fold-resistant, high-barrier polypropylene sheet according to claim 8, characterized in that, The chlorine-containing silane coupling agent is 3-chloropropylmethyldimethoxysilane.
10. A method for preparing the fold-resistant, high-barrier polypropylene sheet according to claim 1, characterized in that, The preparation method includes the following steps: (1) Place the EVOH granules in an 80℃ forced-air drying oven and dry at a constant temperature for 4-6 hours. Dissolve the silane coupling agent in an ethanol aqueous solution with a volume concentration of 70-75% to make the concentration of silane coupling agent in the mixture 8-9wt%. Put the dried EVOH into a high-speed mixer, then add the silane coupling agent ethanol solution and stir at high speed for 10-15 minutes. Then add the polypropylene matrix resin, lubricant, toughening agent, compatibilizer and antioxidant in sequence and dry mix in the high-speed mixer for 3-5 minutes. (2) A co-rotating twin-screw extruder with a length-to-diameter ratio of 40:1 is used. The temperature range is set in 7 sections: Zone 1 185~195℃, Zone 2 200~210℃, Zone 3 215~225℃, Zone 4 220~230℃, Zone 5 215~225℃, Zone 6 210~220℃, and the die head 200~210℃. After the extruded molten strip is cooled and shaped in a 25~35℃ warm water bath, it is fed into a pelletizer to be cut into uniform granules of 3×3mm. The granules are then placed in an 80℃ drying oven for 2 hours to remove residual moisture on the surface and obtain blended granules. (3) The blended granules are fed into a single screw sheet extruder. The barrel temperature is controlled at 190~225℃ and the die lip temperature is set at 210~220℃. After extrusion from the die lip, the material is directly fed into a three-roll calender. The three roll temperatures are set at 50℃, 45℃ and 40℃ respectively. After the shaped sheet is fully cooled by the cooling roller and trimmed, it is wound up to the set length to obtain a fold-resistant, high-barrier polypropylene sheet with a thickness of 0.2~2mm.